Pregabalin as an effective treatment for acute postoperative pain following spinal surgery without major side effects: protocol for a prospective, randomized controlled, double-blinded trial - Ki-Hoon Park; Nam-Su Chung; Hee-Woong Chung; Tae Young Kim; Han-Dong Lee (Trials, 2023)
Abstract Background Patients experience considerable postoperative pain after spinal surgery. As the spine is located at the centre of the body and supports body weight, severe postoperative pain hinders upper body elevation and gait which can lead to various complications, including pulmonary deterioration and pressure sores. It is important to effectively control postoperative pain to prevent such complications. Gabapentinoids are widely used as preemptive multimodal analgesia, but their effects and side effects are dose-dependent. This study was designed to examine the efficacy and side effects of varying doses of postoperative pregabalin for the treatment of postoperative pain after spinal surgery. Methods This is a prospective, randomized controlled, double-blind study. A total of 132 participants will be randomly assigned to the placebo (n = 33) group or to the pregabalin 25 mg (n = 33), 50 mg (n = 33), or 75 mg (n = 33) groups. Each participant will be administered placebo or pregabalin once prior to surgery and every 12 h after surgery for 72 h. The primary outcome will be the visual analogue scale pain score, total dose of administered intravenous patient-controlled analgesia, and frequency of rescue analgesic administered for 72 h from arrival to the general ward after surgery, subdivided into four periods: 1–6 h, 6–24 h, 24–48 h, and 48–72 h. The secondary outcomes will be the incidence and frequency of nausea and vomiting due to intravenous patient-controlled analgesia. Safety will be assessed by monitoring the occurrence of side effects such as sedation, dizziness, headache, visual disturbance, and swelling. Discussion Pregabalin is already widely used as preemptive analgesia and, unlike nonsteroidal anti-inflammatory drugs, is not associated with a risk of nonunion after spinal surgery. A recent meta-analysis demonstrated the analgesic efficacy and opioid-sparing effect of gabapentinoids with significantly decreased risks of nausea, vomiting, and pruritus. This study will provide evidence for the optimal dosage of pregabalin for the treatment of postoperative pain after spinal surgery. Trial registration ClinicalTrials.gov NCT05478382. Registered on 26 July 2022.